The booking problem of a diagnostic resource with multiple patient classes and emergency interruptions. (March 2017) - Zhou, Jie; Li, Jun; Guo, Peng; Lin, Xuemei
Graphical abstract: Highlights: The goal is to improve the total expected reward of the service system. Emergency patients arrive randomly during the service session. The direct waiting time of regular patients is explicitly described. The unit direct waiting cost gradually increases with the previous waiting time. The booking limit number for each patient class is given by marginal analysis. Abstract: CT department is an appointment based service system. All patients except emergency patients should be scheduled in advance. Regular patients arrive on time. Emergency patients arrive randomly and get non-preemptive priority. So the direct waiting time of regular patients should be explicitly described. The unit direct waiting cost gradually increases with the previous waiting time. On the one hand, too many regular patients will increase the direct waiting cost for them and overtime cost for medical resources. On the other hand, too few regular patients will cause idling of medical resources and penalty for delaying regular patients' requests. So a reasonable reservation level should be determined in advance. The booking problem is modeled as a finite horizon Markov decision process. Some booking limit structures are given to improve the total expected reward. The numerical analysis shows that our policies are much better than the policy currently employed.